SOLUTIONS OF SOME PROBLEMS ON RISK AND ITS INSURANCE OPPORTUNITIES IN ACTUARIAL MATHEMATICS (Conferencea, 2022)
This in the article actuary of mathematics important joint calculated insurance risk models light up given , some issues seeing developed